Assignment 12

course mth 163

Your work has been received. Please scroll through the document to see any inserted notes (inserted at the appropriate place in the document, in boldface) and a note at the end. The note at the end of the file will confirm that the file has been reviewed; be sure to read that note. If there is no note at the end, notify the instructor through the Submit Work form, and include the date of the posting to your access page.

assignment #012

.................................................

......!!!!!!!!...................................

21:06:49 `q001. Note that this assignment has 3 questions If we know that y = k x^2, then if (x2/x1) = 7, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE --> y = k x^2 and (x2/x1) = 7, then (y2/y1) = 49 y1 = kx1^2 y2 = kx2^2 (y2/y1) = (x2/x1)^2 (y2/y1) = 7^2 (y2/y1) = 49

.................................................

......!!!!!!!!...................................

21:07:04 If y2 = k x2^2 and y1 = k x1^2, then y2 / y1 = (k x2^2) / ( k x1^2). Since k / k = 1 this is the same as y2 / y1 = x2^2 / x1^2, which is the same as y2 / y1 = (x2 / x1)^2. In words this tells us if y to is proportional to the square of x, then the ratio of y2 to y1 is the same as the square of the ratio of x2 to x1. Now if (x2 / x1) = 7, we see that y2 / y1 = (x2 / x1)^2 = 7^2 = 49.

......!!!!!!!!...................................

RESPONSE --> OK

.................................................

......!!!!!!!!...................................

21:10:31 `q002. If we know that y = k x^3, then if (x2/x1) = 7, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE --> y = k x^3 and (x2/x1) = 7 then (y2/y1) = (x2/x1)^3 (y2/y1) = 7^3 (y2/y1) = 343

.................................................

......!!!!!!!!...................................

21:10:39 If y2 = k x2^3 and y1 = k x1^3, then y2 / y1 = (k x2^3) / ( k x1^3). Since k / k = 1 this is the same as y2 / y1 = x2^3 / x1^3, which is the same as y2 / y1 = (x2 / x1)^3. In words this tells us if y to is proportional to the cube of x, then the ratio of y2 to y1 is the same as the cube of the ratio of x2 to x1. Now if (x2 / x1) = 7, we see that y2 / y1 = (x2 / x1)^3 = 7^3 = 343.

......!!!!!!!!...................................

RESPONSE --> OK

.................................................

......!!!!!!!!...................................

21:30:48 `q003. If we know that y = k x^-2, then if (x2/x1) = 64, what is (y2/y1)?

......!!!!!!!!...................................

RESPONSE --> y = k x^-2 and (x2/x1) = 64 then (y2/y1) = (x2/x1)^-2 (y2/y1) = 64^-2 (y2/y1) = 1/4096

.................................................

......!!!!!!!!...................................

21:30:56 If y2 = k x2^-2 and y1 = k x1^-2, then y2 / y1 = (k x2^-2) / ( k x1^-2). Since k / k = 1 this is the same as y2 / y1 = x2^-2 / x1^-2, which is the same as y2 / y1 = (x2 / x1)^-2, which is the same as 1 / (x2 / x1)^2, which gives us (x1 / x2)^2. So if y = k x^-2, then (y2 / y1) = (x1 / x2)^2.( In words this tells us if y to is inversely proportional to the square of x, then the ratio of y2 to y1 is the same as the square of the ratio of x1 to x2 (note that this is a reciprocal ratio). Now if (x2 / x1) = 64, we see that y2 / y1 = (x1 / x2)^2 = (1/64)^2 = 1/ 4096.

......!!!!!!!!...................................

RESPONSE --> OK

.................................................

Very good work. Let me know if you have questions.